Secular bodies, affects, and emotions : European configurations - Scheer, Monique; Fadil, Nadia; Johansen, Birgitte Schepelern (New York : Bloomsbury Academic, 2019)
"Taking its cue from the study of 'lived religion', Secular Bodies, Affects and Emotions shows how the idea of a secular public is equally marked by a display and cultivation of affect and emotions. Whereas it is widely agreed that religion is often saturated by emotion, the secular is usually treated as a neutral background serving as the domain of public, rational deliberation. This book demonstrates that secularity and secularism are also upheld by bodily practices and emotional attachments. Drawing on empirical case studies, this is the first book to ask and explore whether a secular body exists. Building on the work of Talal Asad, the book argues that the secular is not an absence of religion, but a positive entity that comes about through its co-constitutive relationship with religion. And, once we attune ourselves to recognizing its operations as grammar which structures social practice, writing an anthropology of the secular could become a new possibility."--Bloomsbury Publishing.
List of Figures -- Notes on Contributors -- Acknowledgements -- 1 Secular Embodiments: Mapping an Emergent Field Monique Scheer, Birgitte Schepelern Johansen, Nadia Fadil -- Part 1 Bodies and Other Secular Things -- 2 Contraception and the Coming of Secularism: Reconsidering Reproductive Freedom as Religious Freedom Pamela E. Klassen -- 3 A Secular Corpse? Tracing Cremation in Nineteenth-Century Italy and Germany Carolin Kosuch -- 4 Observing the Atheist at Worship: Ways of Seeing the Secular Body Lois Lee -- 5 Secular Objects and Bodily Affects in the Museum Judith Dehail -- Part 2 Being Secular -- 6 Formations of a Secular Wedding Katie Aston -- 7 Complex Feelings: Catholicism, Gender and the Postsecular Subject in Quebec Geraldine Mossiere -- 8 Secular Self-fashioning against 'Islamization': Beauty Practices and the Crafting of Secular Subjectivities among Middle-Class Women in Istanbul Claudia Liebelt -- 9 Love, War and Secular 'Reasonableness' among hilonim in Israel-Palestine Stacey Gutkowski -- Part 3 Making Secular Citizens -- 10 Secularizing Silent Bodies: Emotional Practices in the Minute's Silence Karsten Lichau -- 11 Required Romance: On Secular Sensibilities in Recent French Marriage and Immigration Regulations J. A. Selby -- 12 Quantitative Knowledge Production on Muslims in Europe as a Practice of 'Secular Suspicion' Birgitte Schepelern Johansen and Riem Spielhaus -- 13 Secular Affect and Urban Exclusion: Feelings about Burkas in Public Spaces Marian Burchardt and Mar Griera -- 14 Afterword: Getting Hold of the Secular Matthew Engelke -- Notes -- References -- Index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Includes bibliographical references and index.
Also issued in print.
Electronic reproduction.
Keywords: Secularism -- Europe; Emotions -- Religious aspects